Prevalence and associated factors of mental and substance use problems among adults in Kenya: A community-based cross-sectional study. - Patrick Nzivo Mwangala; Anita Kerubo; Millicent Makandi; Rachael Odhiambo; Amina Abubakar (PLOS Global Public Health)
Data on the burden and determinants of mental and substance use problems among women in urban and rural informal settlements in Kenya is sparse, thus limiting preventive and treatment efforts in these areas. To bridge the gap, we (a) determined the prevalence of depressive, anxiety and post-traumatic stress disorder (PTSD) symptoms and alcohol and drug use problems among women compared to their spouses and (b) examined the correlates of these outcomes. Data collection for this cross-sectional survey was conducted in 2022 in Mombasa, Kwale and Nairobi counties in Kenya. A total of 1528 adults (1048 women) took part. The 9-Item Patient Health Questionnaire, 7-Item Generalized Anxiety Disorder Scale, Primary Care PTSD Screen for DSM-5, Alcohol Use Disorders Identification Test, and Drug Use Disorders Identification Test were administered alongside other measures. Logistic regression was used to examine the correlates of mental and substance use problems. Overall, the prevalence of mental and substance use problems among women and men respectively was 28% (95% CI 25, 31%) vs 22% (95% CI 18, 26%) [depressive symptoms], 12% (95% CI 10, 14%) vs 8% (95% CI 6, 11%) [general anxiety symptoms], 22% (95% CI 19, 24%) vs 21% (95% CI 17, 25%) [PTSD symptoms], 4% (95% CI 3, 5%) vs 15% (95% CI 12, 19%) [alcohol use problems], and 2% (95% CI 1, 3%) vs 12% (95% CI 9, 15%) [drug use problems]. The prevalence of depressive and anxiety symptoms was significantly higher among women compared to their male counterparts. On the other hand, both current and past-year alcohol and drug use were significantly higher in men than women. Among women, stressful life events, urban residence, food insecurity, family debt, unemployment, poor self-rated health, poor eyesight, and higher educational level were the correlates for elevated depressive, anxiety and PTSD symptoms. Conversely, sexual abuse, living in rented houses, urban residence, verbal abuse, stressful life events, and somatic complaints were the correlates for depressive, anxiety and PTSD symptoms in men. Correlates against mental health problems included social support, higher subjective wellbeing, older age (>50 years), increased vigorous exercise and higher household income (in both sexes). Correlates for current alcohol use in women included stressful life events, urban residence, being sexually active, and living in a single family. Among men, higher household income was associated with current alcohol use. Correlates against current alcohol use included being married, living in a larger household (>5), being a Muslim and having multimorbidity (in both sexes). Correlates for current drug use included unemployment and sexual abuse. Female sex was associated with reduced odds of current drug use. The prevalence of depressive, anxiety and PTSD symptoms, and alcohol use problems is high in the study setting. However, needs vary by gender and study location, highlighting the importance of targeted approaches in mental health services. Our results also highlight the need for integrating mental health services into existing primary care as well as testing and scaling multi-component mental health interventions in this population.